The Role of Microlearning in Lifelong Learning and Its Effectiveness for Generation Z - Sutarman, Sutarman; Riyanto, Slamet; Lesmana, Sri Jaya (The International Journal of Education Management and Sociology, 2025)
This study aims to examine the role of microlearning in lifelong learning and its effectiveness for Generation Z. With the advancement of digital technology, Generation Z, known for their habit of consuming information rapidly and having a shorter attention span, requires a more flexible and efficient learning approach. Microlearning, which delivers content in small, easily digestible chunks, provides a fitting solution to meet these needs. This research explores how microlearning can enhance student engagement, facilitate self-directed learning, and strengthen long-term retention of information. Additionally, the study assesses the potential application of microlearning in regular education, considering the readiness of resources and stakeholders involved. The findings suggest that microlearning is effective in supporting lifelong learning, offering flexibility in terms of time and space, and improving learning outcomes for Generation Z. However, its implementation needs careful preparation with adequate technological support and proper arrangements to ensure optimal impact on the educational process.